2016
DOI: 10.4049/jimmunol.1501849
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: ACVRL1 Signaling Augments CD8α+ Dendritic Cell Development

Abstract: Dendritic cells (DCs) are a collection of different subtypes, each of which is characterized by specific surface markers, gene-expression patterns, and distinct functions. Members of the IFN regulatory factor family play critical roles in DC development and functions. Recently, Irf8 was shown to activate TGF-β signaling, which led to exacerbated neuroinflammation in the experimental autoimmune encephalomyelitis mouse model. We analyzed the effect of Irf8 on TGF-β/bone morphogenetic protein pathway–specific gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Among the inferred target genes of cluster 1.1 that did not overlap with cluster 1.2, Irf2bp2 has been identified as a repressor for IRF2 signaling ( Ramalho-Oliveira et al, 2019 ). In contrast, among the five target genes of cluster 1.2 that were not inferred in cluster 1.1, Cebpb ( Pal et al, 2009 ), Acvrl1 ( Verma et al, 2016 ), Anxa1 ( Yap et al, 2020 ), and Upp1 ( Yan et al, 2016 ) have been reported to be related to IRF signaling and inflammation in various disease models, supporting the argument that cluster 1.2 has the inflammatory osteogenic progenitors mediated by IRF signaling ( Supplementary Figure S8 ).…”
Section: Resultsmentioning
confidence: 59%
“…Among the inferred target genes of cluster 1.1 that did not overlap with cluster 1.2, Irf2bp2 has been identified as a repressor for IRF2 signaling ( Ramalho-Oliveira et al, 2019 ). In contrast, among the five target genes of cluster 1.2 that were not inferred in cluster 1.1, Cebpb ( Pal et al, 2009 ), Acvrl1 ( Verma et al, 2016 ), Anxa1 ( Yap et al, 2020 ), and Upp1 ( Yan et al, 2016 ) have been reported to be related to IRF signaling and inflammation in various disease models, supporting the argument that cluster 1.2 has the inflammatory osteogenic progenitors mediated by IRF signaling ( Supplementary Figure S8 ).…”
Section: Resultsmentioning
confidence: 59%
“…Furthermore, moDCs treated with BMP4 displayed increased immunosuppressive functionality by expressing higher levels of IL-10 and TGFβ ( 13 ). In mice, BMP9 was shown to promote CD8α + DC differentiation and inhibit plasmacytoid DC (pDC) development in a process that is mediated through ACVRL1 ( 14 ).…”
Section: Bmp Regulation Of the Immune Systemmentioning
confidence: 99%
“…Most notably of those, Acvrl1 and St18 which are both involved in cytokine release in the immune system. Acvrl1 signaling is responsible for dendritic cell development within the cytotoxic T cell (CD8 + ) subtype (Verma et al, 2016). This signaling is also related to inflammatory pathways, similarly to RANTES.…”
Section: Network Analysesmentioning
confidence: 99%